Application of Self-Potential Method to Observe Groundwater Flow in Tanjungpura University Area, Pontianak - Muhardi; Kaharudin; Mathaliul Anwar (Universitas Ahmad Dahlan, 2021)
The study aims to observe groundwater flow in the Tanjungpura University area, Pontianak, West Kalimantan. Data collection applied three lines have a length of 65 m, a distance between the lines is 5 m, and a space between the porous pots is 5 m. Each line has 12 points to measure the self-potential value. The results showed that the variation of the self-potential value before the correction was -9.98 mV to 17.24 mV, while after correction, it was -10.52 mV to 16.92 mV. The self-potential distribution shows that the relatively high potential value is in the south, while the low is in the north. The distribution of self-potential values in the study location is caused by groundwater movement, which flows north. In addition, groundwater also flows to the south, especially at 20-30 m from the base station. Thus, the low self-potential value in the north can be used as a reference to identify groundwater accumulation to explore raw water in the study location.